Checklist and Notes on Behavior of Horse Flies (Diptera: Tabanidae) from Marambaia Island, Rio de Janeiro, Brazil, with New Records for the State - Guimaraes, Ronald Rodrigues; Guimarães Júnior, Ronald Rodrigues; Harlan-Rodrigues, Ronald Storti; Guimarães, Roney Rodrigues; Carvalho, Raimuindo Wilson (EntomoBrasilis, 2016)
Abstract. During two periods of studies (1980-1981 and 2012-2013), 31 species of tabanids were identified belonging to 16 genera on Marambaia Island, Rio de Janeiro, Brazil. Esenbeckia lugubris (Macquart), Phaeotabanus cajennensis (Fabricius), Tabanus claripennis (Bigot), Tabanus discus Wiedemann and Tabanus pungens Wiedemann are recorded for the first time in Rio de Janeiro state. Geographical and behavior data of the recorded species are also presented. Inventário e Notas Sobre o Comportamento de Mutucas (Diptera: Tabanidae) na Ilha da Marambaia, Rio de Janeiro, com Novos Registros para o Estado Resumo: Durante dois períodos de estudos (1980-1981 e 2012-2013), foram identificadas 31 espécies de tabanídeos pertencentes a 16 gêneros na Ilha da Marambaia, Rio de Janeiro, Brasil. Esenbeckia lugubris (Macquart), Phaeotabanus cajennensis (Fabricius), Tabanus claripennis (Bigot), Tabanus discus Wiedemann e Tabanus pungens Wiedemann são registrados pela primeira vez no estado do Rio de Janeiro. São apresentados também dados geográficos e de comportamento das espécies registradas.